Fratture periprotesiche di spalla: sintesi vs riprotesizzazione - Novi, M.; Luiso, F.; Paladini, P.; Merolla, G.; Porcellini, G. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC SHOULDER FRACTURES: ORIF VS REVISION ARTHROPLASTYPeriprosthetic fractures in shoulder arthroplasty are a rare occurrence that has been rarely described in the literature.Most of them occur during the surgical procedure, either owing to the surgeon’s inexperience or to poor bone quality.Traumatic fractures affect patients with prostheses who suffer a direct trauma of the operated limb. It is important toassess the clinical presentation of the patient and the radiological findings for correct decision making. The factors thatprompt the choice of treatment are primarily the type of fracture and stem stability. Once the decision has been madeto proceed with either ORIF or revision of the implant, it is important to consider the quality of the rotator cuff inpatients with hemiarthroplasty or total anatomic prosthesis, in order to consider an inverse implant. A long revisionstem, accompanied by bone and cerclage, is always the most appropriate choice to restore function.